Management of diabetes mellitus in tuberculosis patients in Malaysia: a retrospective study - Ibrahim, Ana Afifah (2015)
The prevalence of DM and TB as well as DM in TB cases keeps increasing every year in most of the countries around the world. Many studies have been done in order to explore the association between DM and TB. Due to this converging, WHO and the Union have come out with a guideline named Collaborative Framework for Care and Control of Tuberculosis and Diabetes to guide and educate people in health care setting to manage TB-DM patients. In this study, 100 of patients' medical files were reviewed to assess the prevalence of DM in TB patients, to review the characteristics of TB only and TB-DM patients and also to investigate the current management of DM in TB patients. The prevalence of DM in TB patients was 18%. The number of TB patients was found to be almost equal for both male and female which were 53% and 47% patients respectively. The mean age in TB-DM was 55.5 years which is significantly higher compared to TB only patients which only 39.5. Among all, Malay TB patients were the highest denoted with 49%, followed by other races (31 % ), Chinese (I 6%) and Indian ( 4% ). Most of them were married and employed. Even though TB patients were found to not having critical social habit such as smoking and alcoholic, but both were contributing factors to TB and DM which need to be concerned of. Comparing to TB only patients and TB-DM patients, the percentage of TB-DM patients having co-morbid condition was higher (61.1 %) as compared to TB only patients with only 23.3%. In addition, there was lack of regular blood glucose monitoring at the TB clinic where out of all TB patients, 43% of them were not screened with RBS and insulin was underutilized in the management of DM in TB patients.